2016
DOI: 10.1142/s0217732316500577
|View full text |Cite
|
Sign up to set email alerts
|

The Klein–Gordon equation of a rotating charged hairy black hole in (2 + 1) dimensions

Abstract: In this paper, we consider the Klein-Gordon equation in a 3D charged rotating hairy black hole background to study behavior of a massive scalar field. In the general case we find periodic-like behavior for the scalar field which may be vanishes at the black hole horizon or far from the black hole horizon. For the special cases of non-rotating or near horizon approximation we find radial solution of Klein-Gordon equation in terms of hypergeometric and Kummer functions. Also for the case of uncharged black hole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…In summary, this paper is extension of previous work to include higher order correction to LMP solution, while logarithmic and higher order corrections of KS solution of HL black holes. It is interesting to consider higher order correction of a new regular black hole [107], Myerse-Perry black holes [108], rotating charged hairy black hole [109,110], or five dimensional AdS black hole at N=2 supergravity [111,112].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, this paper is extension of previous work to include higher order correction to LMP solution, while logarithmic and higher order corrections of KS solution of HL black holes. It is interesting to consider higher order correction of a new regular black hole [107], Myerse-Perry black holes [108], rotating charged hairy black hole [109,110], or five dimensional AdS black hole at N=2 supergravity [111,112].…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that presence of logarithmic correction may yields to some stable points at higher dimensional case (d = 10 and d = 11). We can use higher order corrections for the other black holes like Horava-Lifshitz black hole [66,67], several kinds of hairy black holes [68][69][70][71]. In the Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Their result examined for BTZ black holes, anti-de Sitter Schwarzschild and Reissner-Nordstrom black holes in arbitrary dimensions. Such quantum correction applied to several black holes like recently proposed three-dimensional hairy black hole [8][9][10][11][12] and found that it is logarithmic at the first order approximation [13]. In that case the effects of the logarithmic correction on a charged black hole in anti de Sitter space has been studied [14].…”
Section: Introductionmentioning
confidence: 99%